Mental health policy: protecting community mental health during the COVID-19 pandemic - Retno Lestari; Febri Endra Budi Setyawan (SAGE Publishing, 2021)
Despite the growing interest in the treatment and management of COVID-19, communities still end up experiencing multiple stresses with mental health crisis, due to the pandemic. When this is not addressed, it causes stress in the long run, with further mental health damage in individuals and the communities. Furthermore, relevant policy related to the community mental health was identified as awareness in promoting mental issues, yet there are still failures recorded in the aspect of adequately addressing the well-being concerns. This study aims to support community mental health during the crisis, through useful information from relevant articles. It also explains some perspectives from literature reviews, case reports, with society responses from Google Scholar, Science Direct, and Proquest databases concerning recent community mental health issues, and government policy on the impact of the COVID-19 pandemic. The inclusion criteria required articles that were peer-reviewed, by using i) English language March-September 2020; ii) Presented empirical studies related to COVID-19 (quantitative and qualitative); iii) Searched terms related to the general and community mental health, their policy, and COVID-19 pandemic. This study showed 19 articles related to community mental health issues or psychological wellbeing topics. The interventions provided to strengthen community mental health during the pandemic included emergency psychological crisis treatment, hotline assistance, online counseling service with mental care course, and outpatient consultation. Therefore, community mental health issues should be addressed with physical wellness. In addition, the community plays a key role in influencing stakeholders and governments, to increase the priority in supporting mental health.